The role of nutritional support in the physical and functional recovery of critically ill patients: a narrative review - Danielle E. Bear; Liesl Wandrag; Judith L. Merriweather; Bronwen Connolly; Nicholas Hart; Michael P. W. Grocott (Clinical nutrition and metabolism, 2021)
Randomized controlled trials addressing the role of nutrition during long-term recovery from critical illness, including other outcomes, have not shown clear benefits, leading to significant controversy on the topic. Although methodological caveats with failure to adequately appreciate biological mechanisms may explain these disappointing results, it must be acknowledged that nutritional support during early critical illness, when considered alone, may have limited long-term functional impact. This narrative review focuses on recent clinical trials, evaluating the impact of nutrition on long-term physical and functional recovery from critical illness, with specific emphasis on the details of trial design and methodological limitations. Such limitations include delivery of caloric and protein targets, patient heterogeneity, short duration of intervention, inappropriate clinical outcomes, and disregard for baseline nutritional status and intake in the post-ICU period. With survival at the forefront of critical care research, it is imperative that nutrition studies carefully consider biological mechanisms and trial design, which strongly influence long-term physical and functional outcomes among others. Failure to do so may lead to inconclusive clinical trials and consequent rejection of the potential benefits of nutrition interventions during critical illness. This article is the legal Russian-language translation from the original publication of Bear D.E. et al. The role of nutritional support in the physical and functional recovery of critically ill patients: a narrative review in Critical Care [2017;21(1):226. doi: 10.1186/s13054-017-1810-2] with the permission of the copyright holders.